2017
DOI: 10.1017/s000711451700040x
|View full text |Cite
|
Sign up to set email alerts
|

Hb level, iron intake and mortality in Chinese adults: a 10-year follow-up study

Abstract: Anaemia is prevalent in developing countries and is commonly Fe deficiency related. We aimed to assess the association between Fe status, Fe intake and mortality among Chinese adults. We prospectively studied 8291 adults aged 20-98 years with a mean follow-up of 9·9 years. All participants were measured for Hb at baseline in 2002. Food intake, measured by 3-d weighed food record (n 2832), and fasting serum ferritin were measured. We documented 491 deaths (including 192 CVD and 165 cancer deaths) during 81 527 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…This association can also be comparable with previous observations that increased level of sTfR had adverse effects on different health outcomes, including diabetes or insulin resistance (15,32), iron-deficiency anemia (33), and obesity (34). In this study, we also found a U-shaped relationship of Hb and CKD, which is comparable with findings from other health outcomes, such as mortality (35), birth outcome (36), and stroke severity (14).…”
Section: Discussionsupporting
confidence: 92%
“…This association can also be comparable with previous observations that increased level of sTfR had adverse effects on different health outcomes, including diabetes or insulin resistance (15,32), iron-deficiency anemia (33), and obesity (34). In this study, we also found a U-shaped relationship of Hb and CKD, which is comparable with findings from other health outcomes, such as mortality (35), birth outcome (36), and stroke severity (14).…”
Section: Discussionsupporting
confidence: 92%
“…The potential adverse health effects of high iron status in the Chinese population have been studied. For example, high iron status was associated with increased risk of mortality in a 10-y follow-up study in Chinese adults (45). Serum ferritin was positively associated with diabetes risk in several largepopulation studies in China (46)(47)(48)(49)(50)(51)(52), which is consistent with the findings among Western populations.…”
Section: Discussionsupporting
confidence: 77%
“…Studies reported that the inter pregnancy interval [ 22 ] and history of parasitic infection [ 7 , 28 ] were associated with the prevalence of anemia, which could not be estimated in this study due to the lake of the factors. Recent studies noted that both low and high iron intake was associated with mortality among women [ 29 ] and elevated iron level may increase the risk of GDM [ 30 ]. However, the present study did not record the iron supplementation of the participants, which may have impacted the results of adverse pregnancy outcomes of anaemia.…”
Section: Discussionmentioning
confidence: 99%